2022
DOI: 10.1109/access.2022.3206860
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Traceability System From the Users’ Perspective: A Case Study of Thai Coffee Supply Chain

Abstract: We explored the use of blockchain technology for traceability to improve the safety and value of food, focusing on the coffee supply chain as a case study. The main goal was to evaluate the feasibility in terms of design, perceived benefits, and challenges of applying blockchain and traceability from the users' perspective. We implemented a prototype using a user-centered iterative interface design. Then we used the prototype to answer our research questions in mixed-method research, including in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Efficiency gains materialise through blockchain’s streamlined processes for traceability, while the sector’s overall resilience is enhanced. Transparency translates into informed decision-making, enabling businesses to adapt and respond effectively to challenges and changing circumstances (Tharatipyakul et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Efficiency gains materialise through blockchain’s streamlined processes for traceability, while the sector’s overall resilience is enhanced. Transparency translates into informed decision-making, enabling businesses to adapt and respond effectively to challenges and changing circumstances (Tharatipyakul et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To answer RQ3, this study found certain challenges that affect the implementation of blockchain technology despite the benefits highlighted. These challenges include concern over trade secrets disclosures (Rogerson and Parry, 2020; Tharatipyakul et al. , 2022), incomplete or inaccurate information (Tharatipyakul et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations